2021
DOI: 10.3390/ani11092599
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Improved Profitability of Insect-Based Aquafeeds for Farming Nile Tilapia Fish (Oreochromis niloticus L.)

Abstract: In Sub-Saharan Africa, Nile tilapia (Oreochromis niloticus L.) make up over 80% of aquaculture production. However, the local aquaculture farmers are restricted by the unavailability and expensive cost of formulated rations. To reduce reliance on the scarce and expensive fishmeal used in fish feeds, alternative insect protein has been successfully utilized in many aquafeeds. However, data on the influence of insect-based feed on the growth and economic benefit of feeding tilapia with the emerging insect-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Improved growth performance after BSF‐L meal feeding has also been reported in yellow catfish fry (Xiao et al., 2018), rice field eel ( Monopterus albus ) juvenile (Hu et al., 2020) and Siberian sturgeon fingerlings (Rawski et al., 2020). It is noteworthy that replacing FM by using BSF‐L diets at all levels used did not affect survival rate of the fry in this study, similar to results obtained in European sea bass (Abdel‐Tawwab et al., 2020) and Nile tilapia (Wachira et al., 2021). These results indicate that, replacing FM by using BSF‐L meal at 81 to 84% improves growth performance of Nile tilapia fry by enhancing nutrients utilization without affecting the survival rate of the fish.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Improved growth performance after BSF‐L meal feeding has also been reported in yellow catfish fry (Xiao et al., 2018), rice field eel ( Monopterus albus ) juvenile (Hu et al., 2020) and Siberian sturgeon fingerlings (Rawski et al., 2020). It is noteworthy that replacing FM by using BSF‐L diets at all levels used did not affect survival rate of the fry in this study, similar to results obtained in European sea bass (Abdel‐Tawwab et al., 2020) and Nile tilapia (Wachira et al., 2021). These results indicate that, replacing FM by using BSF‐L meal at 81 to 84% improves growth performance of Nile tilapia fry by enhancing nutrients utilization without affecting the survival rate of the fish.…”
Section: Discussionsupporting
confidence: 89%
“…Wachira et al. (2021) reported higher gross profit margin for Nile tilapia fingerlings fed on 100 BSF‐L diet. Moreover, FM replacement with partial defatted black soldier larvae meal (PD‐BSLM) at 25%, 50% and 100% in Nile tilapia juvenile decreased feed cost, increased profit/kilogram gain and resulted in higher economic efficiency (Kishawy et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present finding on reduction in cost with increased levels of H .illucens in O. niloticus diet are consistent with that of Wachira et al (2021) that observed significant cost reduction of use of increased levels of H. illucens in O. niloticus diets as a protein source.…”
Section: Profitability Of Using H Illucens Larva In O Niloticus Dietssupporting
confidence: 92%